Reforming WTO discipline on export duties : sovereignty over natural resources, economic development and environmental protection - Qin Julia Ya (2012)
Seeks to expose the irrationality of the current regime, especially the problems created by the rigid obligations of the several acceding Members. Contends that such obligations deprive these Members of their ownership right to claim a larger share of their natural resources for domestic use and of an effective tool for managing environmental externalities associated with the resource products exported.